(3GdeYGdLGJ GdHbQGWjIs - (3CMeO Hf eMeO CHh GdMSf GdWHQj, fMh (B360 (3g`s
(3ChdgG (B:s
(3hEfgG CaVd GdUfGFY hgh GdWH Ydi GdGNJdGa ajg fbhd(B: (3bO jbSe GdTiF GdfGaY Ydi gPg GdbSeI ajbGd fGaY VQhQi hfGaY ZjQ VQhQi hZjQ fGaY VQhQi hZjQ fGaY ZjQ VQhQi cGdfaS ai GdMjhGf s
(3BNQgG (B:s
(3aEf eUfaj GdcfGfjT bUQhG ai gPG GdfhY, hGfeG jSJNQL gPG ef cdGe LGdjfhS hGfeG GdChdi hGdGTHg ai SGFQ GdYdGLGJ JJNPGOdJg ef GdGYQGVJeJ GdebGdI GdYGTQI s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3hgj JMJhi Ydi YTQ ebGdGJs
(3cd ebGdI ebSeI Edi aUhd s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdWHs